Developing Intercultural Competence through Children’s Literature in German Language Learning - Andina Meutia Hawa; Anne Pratiwi; Dyani Prades Pratiwi; Fakhria Nesa; Roma Kyo Kae Saniro; Ahmad Hamidi (Universitas Islam Sumatera Utara, 2026)
Mastering a foreign language requires not only linguistic skills but also the development of intercultural competence. This study aims to analyze the use of the German children's novel entitled Emil und die Detektive by Erich Kästner as a medium for developing students' intercultural competence in German language learning in Indonesia. This study uses a descriptive qualitative approach with thematic analysis of literary works. Data in the form of narratives, dialogues, and character actions were collected through listening and note-taking, then analyzed using literary analysis with reference to Michael Byram's Intercultural Communicative Competence (ICC) framework. Data validity was strengthened through triangulation of sources and theories. The results of the study indicate that the novel Emil und die Detektive embodies values of intercultural understanding, such as independence, solidarity, honesty, vigilance, and equal relations between children and adults. These values have the potential to be integrated into German language learning through discussion activities, interpretive writing, and literary appreciation. Therefore, language learning is not only oriented towards linguistic mastery but also contributes to the development of empathy, interpretation skills, cross-cultural interaction, and critical cultural awareness in line with Byram's ICC model.